Effects of different doses of rosemary oil (Rosmarinus officinalis L.) on oxidative stress and apoptosis of liver of heat stressed quails - Ozcelik, Mehtap; Simsek, Ulku Gulcihan; Ceribasi, Songul; Ciftci, M. (Eugen Ulmer Gmbh Co, 2014)
This study was conducted to determine the effects of chronic heat stress (HS) on oxidative stress parameters, histopathological lesions of liver associated with the oxidative stress and protective effect of rosemary (Rosmarinus officinalis L.) oil supplementation at the doses of 125 and 250 mg/kg. A total of 180 fifteen-days-old Japanese quails were randomly allocated into 6 groups consisting of 10 birds of 3 replicates each. Malondialdehyde (MDA) levels of all tissues and serum increased in the HS group in contrast to the control (TN) (P < 0.05). Dose of 125 mg/kg rosemary oil reduced MDA levels of tissues and serum in the HS group (P < 0.05), but not in TN condition (P > 0.05). Dose of 250 mg/kg rosemary oil decreased MDA level of serum (P < 0.05). Rosemary oil enhanced SOD production of serum in both HS and TN groups (P < 0.05). GSH-Px activities of serum and liver were significantly higher in TN group than in HS group (P < 0.05). The dose of 125 mg/kg rosemary oil significantly enhanced the GSH-Px activities in heart, liver and kidney in different environmental conditions (P < 0.05). The rosemary oil supplementation also increased the GSH production of liver, serum and heart tissues (P < 0.05). Heat stress induced Kupffer cell activation, fatty degeneration, accumulation of bile pigment, extra-medullar hematopoesis and hepatocyte apoptotic index of liver (P < 0.05). The dose of 125 mg/kg rosemary oil resulted in a significant recuperation of these parameters in the HS group (P < 0.05), but dose of 250 mg/kg rosemary oil aggravated these phenomena in both environmental conditions (P < 0.05). In conclusion, the results of this study clearly suggested that 125 mg/kg rosemary oil supplementation diminished HS induced oxidative stress by its potent antioxidant activity. Dose of 250 mg/kg rosemary oil showed hepatotoxic effect and increased apoptotic cell index of liver.
Einfluss verschiedener Zulagenhöhen an Rosmarinöl (Rosmarinus officinalis L.) zum Futter auf den oxidativen Stress und die Leber-Apoptose bei Hitze-gestressten Wachteln
Keywords: Quail; nutrition; heat stress; rosemary oil; oxidative stress; apoptosis